Immunohistochemical expression of TWIST and H-TERT in benign and malignant prostatic lesions. Issue 1 (July 2016) - Salama, Maha E.; Ibrahim, Wael S.
Abstract : Introduction: Carcinoma of the prostate is the most common visceral cancer in men, ranking as the second most common cause of cancer-related deaths in men older than 50 years of age, after carcinoma of the lung. The diagnosis of prostatic adenocarcinoma, especially on needle biopsy, can occasionally be challenging. Immunohistochemistry has emerged as an important tool that can aid in confirming the diagnosis of minimal carcinoma and/or distinguishing between prostatic adenocarcinoma and its mimickers. Aim of the work: In this study, we attempted to evaluate the diagnostic and prognostic roles of TWIST and H-TERT expression in prostatic carcinoma and its mimickers. Materials and methods: Paraffin blocks of 48 prostatic carcinoma specimens, with and without other lesions, were collected and studied histologically using hematoxylin and eosin stains and immunohistochemically using antibodies against TWIST and H-TERT. Results: Both TWIST and H-TERT showed a statistically significant difference in their expression between benign prostatic hyperplasia (BPH) and prostatic carcinoma on the one hand and BPH and prostatic intraepithelial neoplasia (PIN) on the other. Moreover, H-TERT showed a statistically significant difference in its expression between PIN and prostatic carcinoma. A significant correlation with increasing Gleason score was achieved in H-TERT expression only. Conclusion: TWIST expression can be used to differentiate between BPH and PIN, but not between PIN and prostatic carcinoma, whereas H-TERT proved to be more useful in differentiating between BPH, PIN, and carcinoma, besides its prognostic value, as it correlates significantly with the Gleason score.